1983
DOI: 10.1016/0010-7824(83)90053-7
|View full text |Cite
|
Sign up to set email alerts
|

Fertility regulation in nursing women: V. Long-term influence of a low-dose combined oral contraceptive initiated at day 90 postpartum upon lactation and infant growth

Abstract: The study was designed to test the long-term influence of a low-dose oral contraceptive upon lactation and infant growth when treatment was initiated at day 90 postpartum. The contraceptive tested contained ethinyl estradiol 0.03 mg and levonorgestrel 0.15 mg. The control group was formed by women who chose non-hormonal contraception at the same postpartum time. Only cases who were in exclusive breast-feeding with a minimal infant daily weight increase of 20 g per day during the third month of age were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 5 publications
1
12
0
2
Order By: Relevance
“…Among studies examining COCs initiated at ≥ 6 weeks postpartum, results were consistent with regard to infant outcomes, with no articles finding differences in either infant growth or health. Newly identified articles reporting infant outcomes [16,22] were consistent with those previously identified [15,[25][26][27].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Among studies examining COCs initiated at ≥ 6 weeks postpartum, results were consistent with regard to infant outcomes, with no articles finding differences in either infant growth or health. Newly identified articles reporting infant outcomes [16,22] were consistent with those previously identified [15,[25][26][27].…”
Section: Discussionsupporting
confidence: 71%
“…1 and Table 1) [11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Of these articles, 10 [11,12,15,[18][19][20][24][25][26][27] were described in a previous review [8], 3 were newly identified for this review but originally published before 1973, and 2 were published since the last review [16,17,[21][22][23]. All included articles reported on women using COCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetten, Kalzium, Natrium, Kalium und Magnesium deutlich ab; dies führt zu einer Minderwertigkeit der Muttermilch [61], Ein Übertritt der verabreichten Östrogene vom Plasma der Mutter in die Muttermilch und damit zum Kind findet statt [58]. Bei vollem Stillen, d.h. ungefähr 600 ml Milchmenge pro Tag.…”
Section: Ovulationshemmerunclassified
“…Die relative Gewichtszunahme war dabei in der ersten Gruppe deutlich geringer [61 ]. Generell sollten Ovu lationshemmer wegen der allgemein erhöhten Thrombosegefahr im Früh wochenbett nicht zu früh abgegeben werden [64], Es erstaunt nicht, dass heute über 50% der Mütter, die postpartal die Pille nahmen, diese innerhalb eines Zeitraumes von 7 Monaten postpartal wieder sistiert haben [5], ja sogar, dass das kürzeste graviditätsfreie Intervall gerade bei denjenigen Frauen anzutreffen war, die Ovulationshemmer im Wochenbett eingenommen haben [12], Bei der Beratung ist, was die Ovu lationshemmer angeht, auch dieser Punkt mit zu berücksichtigen.…”
Section: Ovulationshemmerunclassified